Analysis of the Impact of Modernization of Baduy Tribe Customary Law in the Modern Era - Pradipta, Aditya Dimas; Nasution, Habibah Sari; Siregar, Ahmad Ansari (CV. Rayyan Dwi Bharata, 2024)
Modernization is the change or rather the process of changing traditional society into a modern society. Modernization has the main goal of improving the welfare of the general public, by improving several socio-cultural aspects that exist in society. Our country, Indonesia is an archipelago that has around 17 thousand islands and there are still islands that do not have their identity, with as many islands as Indonesia has a population of nearly 280 million people and has a variety of ethnic and cultural diversity. Moreover, the customs or habits of each community in Indonesia must be diverse and will certainly continue to develop as the times progress. But not all follow the times, there are still some areas in Indonesia that still hold tightly to their customs to this day. One of them is found in the inland area of Lebak Regency, Banten Province. Namely the Baduy tribe, from several videos that I saw, I tried to explain the Baduy customary law and culture in detail as the community changes there due to modernization. The Baduy tribe has a lot of uniqueness that we can learn and apply in our lives. The Baduy tribe is different from the tribes in Indonesia, the Baduy tribe is very difficult to accept modernization that has developed until now, therefore the Baduy tribe is divided into two settlement groups, namely Baduy Dalam and Baduy Baduy.